Operations Upgrading of Community Enterprises of Organic Agriculture Promotion Group, U Thong District, Suphanburi Province - Yongphet, Piyaphong; Nakpibal, Pinyapat; Kaewpuang, Teadkait; Phunphon, Trimas; Taksima, Takunrat; Yongphet, Phatchara; Diskajun, Kanokporn (Area Based Development Research Journal, 2022)
The Organic Agriculture Promotion Group, U Thong district, Suphanburi province is reportedly a community facing agricultural problems caused by drought and floods. It also faces the considerable production cost of rice fields and agricultural areas because of soaring fertilizer and pesticide prices. These lead to debt problems for people in the community along with effects on their health and the environment. Therefore, the objective of this research is to transfer knowledge, build, and develop skills of community innovators as proficient in organic farming innovation and technology. In addition, a mechanism for transforming organic agriculture into a community enterprise network comprising 13 local households is proposed through a 5-step process: 1) sustainable grouping, 2) process management throughout the supply chain, 3) community learning and innovation, 4) community product development and 5) marketing and promoting community networking. With the support of a joint network between public and private organizations, we are encouraged to solve agricultural problems to build up strength and sustainability through the application of the principles of sustainable and self-reliant farmer career development in the dimension of the sustainable community development plan (3ES+M). Specifically, we have applied innovations and technologies—i.e., a dry noodles machine, a solar insect trap, a solar drying cabinet entitled "Hlungtao model", and an accelerator for decomposing agricultural waste materials to promote the operations of the community enterprise group. The results showed that such innovations and technologies can solve problems in organic farming, reduce the burden concerning fertilizer and pesticide costs by 100%, and increase their income by 60-80%. In summary, a participatory spatial development operation mechanism has been created, resulting in an increasing number of participants in 18 households and the emergence of 15 community innovators with expertise in creating, developing and maintaining innovations and technologies. These community innovators, as resource persons, are capable of spreading knowledge to the interested public to promote sustainability in everyday living.